2010
DOI: 10.1073/pnas.1008573107
|View full text |Cite
|
Sign up to set email alerts
|

In an early branching metazoan, bacterial colonization of the embryo is controlled by maternal antimicrobial peptides

Abstract: Early embryos of many organisms develop outside the mother and are immediately confronted with myriads of potential colonizers. How these naive developmental stages control and shape the bacterial colonization is largely unknown. Here we show that early embryonic stages of the basal metazoan Hydra are able to control bacterial colonization by using maternal antimicrobial peptides. Antimicrobial peptides of the periculin family selecting for a specific bacterial colonization during embryogenesis are produced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 128 publications
(133 citation statements)
references
References 41 publications
3
127
1
2
Order By: Relevance
“…1e-h). Although periculin expression is activated not only during oogenesis but also by a number of environmental signals 23 , the observation of tumour cells expressing both Cnnos1 and periculin supports the view that tumour cells are committed to the female germline. A quantitative morphological analysis showed that the cells within tumours are predominantly large ISCs 19 (Fig.…”
Section: Morphology and Histologysupporting
confidence: 48%
See 3 more Smart Citations
“…1e-h). Although periculin expression is activated not only during oogenesis but also by a number of environmental signals 23 , the observation of tumour cells expressing both Cnnos1 and periculin supports the view that tumour cells are committed to the female germline. A quantitative morphological analysis showed that the cells within tumours are predominantly large ISCs 19 (Fig.…”
Section: Morphology and Histologysupporting
confidence: 48%
“…This polyclonal antibody that was raised against periculin1a in Hydra vulgaris recognizes multiple paralogues of periculin 23 . This property of the antipericulin antibody, the presence of at least four periculin paralogues in H. oligactis and possible expression of some of the periculin paralogues outside the context of female germline preclude any firm conclusion about cellular origin of the tumour cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in mice have shown that the expression level of AMPs of the α-defensin family greatly affects community composition (25). In the cnidarian Hydra, sequentially expressed AMPs of the periculin family mediate the establishment of the bacterial microbiota during embryogenesis (27).…”
mentioning
confidence: 99%